Silicon Photonic Bragg Grating Structures for Spectral Filtering. - Ortega-Moñux, Alejandro; Fernández-Hinestrosa, Alejandro; Pérez-Armenta, Carlos; Luque-González, José Manuel; Sánchez-Postigo, Alejandro; Pereira-Martín, Daniel; Wanguemert-Pérez, Juan Gonzalo; Halir, Robert; Hadij-El-Houati, Abdelfettah; Cheben, Pavel; Schmid, Jens H.; Milanizadeh, M.; et al. (My University, 2024)
Integrated optical filters play a key role in modern optical systems, finding extensive applications in quantum optics, biosensing, programmable photonics, and telecommunications. Among the most commonly used structures utilized for implementing integrated optical filters are ring resonators and Bragg gratings. Bragg gratings are characterized by a periodically perturbed refractive index profile along the propagation direction. By precisely engineering the strength of the perturbation along the grating length, filters with arbitrary spectral responses can be achieved. In this work we summarize our recent contributions to integrated Bragg filters in Si-photonics, covering designs for applications ranging from telecommunications to quantum optics.
Keywords: Optica integrada; Fotónica; Silicio; Guías de ondas; Silicon photonics; Integrated optics; Subwavelength gratings; Waveguides; Integrated Bragg Gratings